The Exclusive Remedy Provision in Canadian Worker Compensation Law: The Need for Legislative Reform - West, Leigh (Relations industrielles / Industrial Relations, 1988)
This paper examines the effect and the constitutionality of the statutory bar as it impacts on workers and their dependents and comments on the significance and the merits of the constitutional challenges to the statutory bar which have already emerged. Statutory reforms which would help alleviate the strains while preserving intact the integrity of the worker compensation system are briefly reviewed.